The Impact of Characteristics of the Board of Directors on the Timelines of Corporate Internet Reporting Index of Companies in Indonesia. Issue 1 (June 2022) - Kiswanto,; Setiawan, Doddy
The development of information technology supports companies in conveying information to all stakeholders in a timely way. This study examined corporate internet reporting that was influenced by the characteristics of the directors (Size, Indep, Aboard, Fboard, Tenur, Famboard, Gender and Founder) of Indonesian companies. Furthermore, this study used the ordinary least square analysis technique which presented five control variables: firm size, profitability, leverage, liquidity and firm age. The research sample is 513 companies of the 716 companies listed on the Indonesia Stock Exchange. The results show that board of directors' size, independent board of directors, tenure, family relations and gender have a significant effect on timeliness of corporate internet reporting (TCIR), while age of president director, foreign director and founder do not have a significant effect. Therefore, firm size, profitability and liquidity are able to be control variables on the use of TCIR through the company's web, while leverage and firm age are not able to do this. Therefore, it is advisable for companies in Indonesia to pay attention to the composition of the characteristics directors in order to improve the quality of company financial information via the internet. This needs to be done because it can give a positive signal to all stakeholders, which will ultimately increase stakeholder trust in the company.